2000
DOI: 10.1364/ol.25.001261
|View full text |Cite
|
Sign up to set email alerts
|

Fast photorefractive response in B_12SiO_20 in the near infrared

Abstract: The polarization self-modulation effect was applied for effective measurement of the characteristic response time of nominally pure Bi(12)SiO(20) (BSO) at wavelengths of 810 and 980 nm. Owing to oxygen deficiency in the crystal lattice, the BSO crystals showed unusual photorefractive sensitivity and remarkable operation speed in the near-infrared spectral region. A response time of 130 ms was measured at 810 nm, and a response time of 540 ms was measured at 980 nm, with incident intensities of 110 and 200mW/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Optically pumping the electrons with gating light is recognized method to enhance the near-infrared properties of sillenites [8]. Some authors assigned the observed transient character during holographic recording to simultaneous electron-hole gratings competition [9,10]. Generally, the anti-site Bi defect (known as Bi 3+ Si + h center upon illumination assuming n-type photoconductivity), is identified as the main photorefractive defect in sillenite structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optically pumping the electrons with gating light is recognized method to enhance the near-infrared properties of sillenites [8]. Some authors assigned the observed transient character during holographic recording to simultaneous electron-hole gratings competition [9,10]. Generally, the anti-site Bi defect (known as Bi 3+ Si + h center upon illumination assuming n-type photoconductivity), is identified as the main photorefractive defect in sillenite structure.…”
Section: Methodsmentioning
confidence: 99%
“…Later on, improved NIR recording and extended lifetime has been achieved in un-doped BTO due to the hole-based complementary grating after green light pre-exposure [9]. At the same time, a modification of sillenite's structure by reduction/oxidation treatments [10] or by adding suitable dopants have been done [11,12]. For example, Ru addition shows prospective features for energy transfer and twobeam coupling efficiency enhancement [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They find wide applications in real-time holography, optical information processing, holographic interferometry, …etc [1][2][3]. Recently, special attention is focused on near infrared (NIR) sensitivity improvement [4][5][6][7], which is of essential technological interest since it allows utilization of cheap diode lasers in photorefractive devices development for optical fiber communication as well as of particular importance for non-destructive biological object testing.…”
Section: Introductionmentioning
confidence: 99%
“…Two possible ways to extend the sensitivity to the NIR spectral range were demonstrated by affecting the growth conditions of sillenite crystals to increase oxygen defects concentration [4][5][6], as well as by introducing suitable doping elements into the crystal structure. We reported that Ruthenium (Ru) is an appropriate dopant, which significantly improves the NIR sensitivity of Bi 12 TiO 20 (BTO) [7].…”
Section: Introductionmentioning
confidence: 99%